Comparison between distance and near visual acuity in amblyopes. Issue 46 (13th November 2020) - Chun, Heejeong; Lee, Young Chun
Abstract : Abstract: To compare distant visual acuity (DVA) and near visual acuity (NVA) in amblyopia and evaluate if NVA can be used to diagnose amblyopia. A retrospective study was performed on 73 patients diagnosed with amblyopia based on DVA, by measuring their NVA and comparing the DVA and NVA. The NVA was measured by Snellen chart at 30 cm and the DVA was measured by Dr Hahn vision test chart at 5m. The patients' age, type of amblyopia, spherical equivalent, the difference between spherical equivalent and the fellow eye spherical equivalent spherical, and prism diopter (PD) were evaluated and their relationship with the difference between the DVA and NVA was analyzed. The NVA was significantly better than the DVA in amblyopia ( P = .000). The difference between the DVA and NVA was not significantly related to the type of amblyopia ( P = .600) or the patients' age( P = .351). Also, the difference between the DVA and NVA was not significantly affected by the spherical equivalent ( P = .425) or the difference between spherical equivalent and the fellow eye spherical equivalent ( P = .212) in anisometropia amblyopia, and also not by the PD ( P = .882) in strabismus amblyopia. In amblyopes, the NVA was better than the DVA before amblyopia treatment. The difference between the DVA and NVA was not affected by age, type of amblyopia, spherical equivalent, the difference between spherical equivalent and the fellow eye spherical equivalent spherical, or PD. Therefore, it should be taken into consideration that NVA could underestimate the severity of amblyopia and affect the accuracy at diagnosing amblyopia.